Acute Cigarette Smoking Reduces Vasodilative Effect Induced by Sympathetic Block in Dogs. Issue 1 (1st January 2001) - Kitajima, Toshimitsu; Okuda, Yasuhisa; Mishio, Mutsuo; Hamaguchi, Shinsuke; Yamaguchi, Shigeki; Kimura, Yoshiyuki
Abstract : Background and Objectives: The aim of this study is to clarify the influence of acute cigarette smoking on vasodilation induced by sympathetic block. Methods: We measured mean arterial pressure, heart rate, left brachial artery blood flow (BABF), right femoral artery blood flow (FABF), and plasma catecholamines in dogs to examine the effect of acute cigarette smoking after stellate ganglion block (SGB). The experimental protocol was: (1) Left SGB using 1.0 mL 0.5% mepivacaine without smoking (sham smoking); and (2) left SGB using 1.0 mL 0.5% mepivacaine followed by a single cigarette smoking (nicotine 1 mg) 15 minutes after the block. Results: SGB induced a significant increase of BABF during the study (baseline, 100%; peak at 10 minutes after SGB, 176% ± 9%; P < .05) in sham smoking and a significant decrease of FABF from 10 minutes after the block to 20 minutes after sham smoking (baseline, 100%; bottom at 5 minutes after sham smoking, 82% ± 8%; P < .05). Smoking after SGB induced a significant decrease of BABF 60 minutes after smoking (baseline, 100%; 69% ± 11%; P < .05) and a significant decrease of FABF during the study (baseline, 100%; bottom at 20 minutes after smoking, 74% ± 20%; P < .05). Smoking significantly increased plasma norepinephrine and epinephrine through the study. Conclusions: Sympathetic block induces a significant increase of peripheral blood flow, but smoking produces a significant decrease in the blood flow in the SGB-induced dilated vessels.